Mengembalikan Kesejatian Peran Orang Tua dalam Pendidikan Anak: Sebuah Tinjauan Konseptual: Restoring the Authentic Role of Parents in Children's Education: A Conceptual Review - Azwar, Azwar; Abur Hamdi Usman (Litera Academica Publishing, 2025)
This study aims to explore the true essence of the parental role in the tarbiyah (Islamic education) of children from an Islamic perspective, which is seen not merely as a biological or administrative responsibility, but as a sacred trust in shaping the child’s character, spirituality, and personality. The study also identifies the factors contributing to the weakening of parental roles in child education in the contemporary era and formulates a conceptual framework to restore this authentic role in accordance with Islamic values. The research employs a qualitative approach through library research and conceptual review, analyzing classical and contemporary literature, the Qur’an, hadiths, and relevant scholarly works using content analysis techniques. Findings show that in Islam, the parental role encompasses spiritual, intellectual, emotional, social, and cultural dimensions. Scholars such as Al-Ghazali and Ibn Qayyim emphasize the importance of early education grounded in tawheed (monotheism) and akhlaq (morality). Meanwhile, digitalization, lifestyle shifts, and the erosion of religious values are among the key factors diminishing parental involvement today. The proposed conceptual framework offers foundational principles and contextual approaches for nurturing children within an Islamic framework. Theoretically, this study enriches the discourse of Islamic education; practically, its findings provide a foundation for designing family education policies and Islamic parenting programs that are both contextual and responsive to contemporary challenges.